Fundamentals of biochemistry - Donald Voet; Voet, Judith; Pratt, Charlotte W; Heilman, Destin; Woski, Stephen (New Delhi Wiley, 2026)
Life cells and thermodynamics; Physical and chemical properties of water; Amino acids the building blocks of proteins; Proteins structure and folding; Carbohydrates Nucleotides nucleic acids and genetic information Lipids bilayers and membranes; Passive and active transport
Keywords: Biochemistry